PENGARUH PENINGKATAN KONSENTRASI AMONIUM TERHADAP PERKEMB ANGAN Meloidogynejavanica PADA KULTUR AKAR TOMAT - Sudirman Sudirman (BERITA BIOLOGI, 2009)
Research was aimed at knowing the effect of increasing ammonium concentrations on Meloidogyne javanica development in tomato roots growing in axenic culture.Egg masses of M. javanica were exposed to deficient ammonium concentration (1.5 ppm NH/) in a nutrient agar medium upon which tomato roots were growing. One week after inoculation, stages of nematode development were recorded and infected tomato roots were aseptically transferred into nutrient agar media with four different ammonium concentrations (1.5. 9.0. 54 and 324 ppm NH/). Stages of nematode development inside roots were then observed at weekly interval for three weeks. Results of the research showed that increasing ammonium concentration after root infection suppressed nematode development. In roots transferred to high ammonium concentrations, fewer nematodes matured and most of those that did were males. In addition, there were also fewer galls and lower root dry weights in increased ammonium than those with constant low ammonium concentration.